Numerical modelling of major planets movement on the new interaction principle basis - Anatolii F Zausaev (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2011)
Numerical integration of the equations of movement of major planets, on the basis of a new principle of interaction is spent. Elements of orbits of major planets on large time interval (1602-2200) are calculated. Results of calculations are compared with elements of the orbits deﬁned according to coordinates and speeds by numerical theory DE405. It is shown that elements of orbits of the exterior planets, found on new algorithm, will well be coordinated with dates DE405. For internal planets Venus, the Earth and Mars have insigniﬁcant discrepancies in secular oﬀsets of perihelions in comparison with dates DE405.